1993
DOI: 10.1021/ma00064a006
|View full text |Cite
|
Sign up to set email alerts
|

X-ray studies on the structure of polyacrylonitrile fibers

Abstract: Using an X-ray fiber diffractometer, 2D intensity distributions of homopolymer polyacrylonitrile (PAN) fibers are measured in reciprocal space in the plane containing the fiber axis. The equatorial intensity distributions show four relatively sharp reflections and three diffuse maxima. The sharp reflections correspond to a pseudohexagonal 2D lattice of intermolecular packing. The diffuse maxima are due to the Laue scattering of a rotational disorder in this lattice. The off-equatorial intensity distribution is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
144
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(157 citation statements)
references
References 18 publications
13
144
0
Order By: Relevance
“…It is reasonable that application of a large electric field aids in the alignment of monomer dipoles, which suffer from the disorder caused by the random kinking down the polymer chain, and thus helping to stabilize a polar phase. Liu and Roland [81] found no evidence for the coexistence of multiple phases, as is the case in untreated cast PVDF films, in which polymorphous films possess regions of both all-trans and trans-gauche conformation [81,84]. Further, piezoelectric studies have shown that stretching PAN fibers results increases the piezoelectric response, which, again, is consistent with the "unkinking" of the polymer chains (removing gauche bonds) due to strain.…”
Section: Cyanopolymersmentioning
confidence: 99%
See 4 more Smart Citations
“…It is reasonable that application of a large electric field aids in the alignment of monomer dipoles, which suffer from the disorder caused by the random kinking down the polymer chain, and thus helping to stabilize a polar phase. Liu and Roland [81] found no evidence for the coexistence of multiple phases, as is the case in untreated cast PVDF films, in which polymorphous films possess regions of both all-trans and trans-gauche conformation [81,84]. Further, piezoelectric studies have shown that stretching PAN fibers results increases the piezoelectric response, which, again, is consistent with the "unkinking" of the polymer chains (removing gauche bonds) due to strain.…”
Section: Cyanopolymersmentioning
confidence: 99%
“…Another system that has proven fruitful in the study of ferroelectricity and electroactivity in cyanopolymers is that of polyacrylonitrile, PAN [79][80][81]. Although similar to PVDCN, PAN has only one cyano group per monomer, with the missing -C≡N group replaced by a single hydrogen atom, as shown in Figure 7a.…”
Section: Cyanopolymersmentioning
confidence: 99%
See 3 more Smart Citations